1, 2-dithioglycol functionalised carbon nitride quantum dots as a "turn – off" fluorescent sensor for mercury ion detection. Issue 8 (21st June 2019) - Wang, Jun; Cao, Yu; Wang, Chengyin; Chong, Hui; Wang, Guoxiu
ABSTRACT: A kind of 1, 2-dithioglycol (DTG) functionalised carbon nitride quantum dots (DTG-CNQDs) was designed for the first time by modifying DTG on the surface of carbon nitride quantum dots (CNQDs). The as-prepared DTG-CNQDs exhibit strong blue fluorescence under ultraviolet light and have a high quantum yield of 27%. Experiments show that Hg 2+ has a good quenching effect on the fluorescence of DTG-CNQDs. In phosphate buffer (PBS, 10 mM, pH 6.0), the fluorescence quenching rate (F0 /F) has a good linear relationship with the concentration of Hg 2+ in the range of 0.020–0.50 μM with detection limit of 0.63 nM. This fluorescent probe possesses high sensitivity and good selectivity, which can be applied in the rapid detection of Hg 2+ in tap and lake water samples.